2023
DOI: 10.3390/v15030745
|View full text |Cite
|
Sign up to set email alerts
|

Human Brain Microvascular Endothelial Cells Exposure to SARS-CoV-2 Leads to Inflammatory Activation through NF-κB Non-Canonical Pathway and Mitochondrial Remodeling

Abstract: Neurological effects of COVID-19 and long-COVID-19, as well as neuroinvasion by SARS-CoV-2, still pose several questions and are of both clinical and scientific relevance. We described the cellular and molecular effects of the human brain microvascular endothelial cells (HBMECs) in vitro exposure by SARS-CoV-2 to understand the underlying mechanisms of viral transmigration through the blood–brain barrier. Despite the low to non-productive viral replication, SARS-CoV-2-exposed cultures displayed increased immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 136 publications
1
12
0
Order By: Relevance
“…We observed an increase in brain endothelial cell VCAM-1 in acute SARS-CoV-2 infection. This is similar to reports of upregulated leukocyte adhesion molecules in the cerebrovasculature of patients with severe acute COVID-19 (Savarraj et al, 2021; Thakur et al, 2023; Zhou et al, 2021) and in cultured brain endothelial cells exposed to SARS-CoV-2 virions or proteins (Buzhdygan et al, 2020; Constant et al, 2021; Motta et al, 2023; Yang et al, 2022). These findings fit within a larger context of brain endothelial hyperinflammatory responses and systemic inflammation in COVID-19 (Bonetto et al, 2022; Frere et al, 2022; Israelow et al, 2020; Pilotto et al, 2021; Rutkai et al, 2022; Soung et al ., 2022).…”
Section: Discussionsupporting
confidence: 90%
“…We observed an increase in brain endothelial cell VCAM-1 in acute SARS-CoV-2 infection. This is similar to reports of upregulated leukocyte adhesion molecules in the cerebrovasculature of patients with severe acute COVID-19 (Savarraj et al, 2021; Thakur et al, 2023; Zhou et al, 2021) and in cultured brain endothelial cells exposed to SARS-CoV-2 virions or proteins (Buzhdygan et al, 2020; Constant et al, 2021; Motta et al, 2023; Yang et al, 2022). These findings fit within a larger context of brain endothelial hyperinflammatory responses and systemic inflammation in COVID-19 (Bonetto et al, 2022; Frere et al, 2022; Israelow et al, 2020; Pilotto et al, 2021; Rutkai et al, 2022; Soung et al ., 2022).…”
Section: Discussionsupporting
confidence: 90%
“…We have previously shown that cells of the NVU express the known receptors required for SARS-CoV-2 to enter host cells, including ACE2 and TMPRSS2 [ 6 ]. However, several laboratories, including our group, failed to demonstrate any productive SARS-CoV-2 replication in brain endothelial cells [ 38 ], [ 39 ], [ 40 ]. While a productive infection has recently been reported in human induced pluripotent stem cell-derived brain capillary endothelial-like cells, this was achieved only after employing a high multiplicity of infection (MOI) 10, which questions the pathological relevance of these findings [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 is a key cytokine in BBB integrity and is a hallmark of neuroinflammatory processes [ 44 ]. Our group published recently that immortalized HBMEC exposed to SARS-CoV-2 have increased IL-6 gene expression [ 38 ]. The results of the current study indicate that treatment of HBMEC with the S1 subunit markedly upregulated the release of IL-6.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to bacteria, systemic viral infections often lead to marked expression of proinflammatory cytokines and vascular complications, such as thrombosis and/or hypoxemia ( Ishiguro et al, 2019 ; Pajo et al, 2021 ; Neufeldt et al, 2022 ; Motta et al, 2023 ). A recent example of this is infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus, the etiological agent of coronavirus disease 2019 (COVID-19).…”
Section: Systemic Inflammationmentioning
confidence: 99%